2016
DOI: 10.1055/s-0042-111515
|View full text |Cite
|
Sign up to set email alerts
|

Luseogliflozin, A Sodium Glucose Co-transporter 2 Inhibitor, Alleviates Hepatic Impairment in Japanese Patients with Type 2 Diabetes

Abstract: Luseogliflozin, a selective inhibitor of sodium glucose co-transporter 2 (SGLT2), was previously shown to improve the blood glucose and hemoglobin A1c (HbA1c) levels of patients with type 2 diabetes in a clinical setting. Although patients with type 2 diabetes often have hepatic impairment, few reports have been published concerning the influence of luseogliflozin on HbA1c and hepatic function in patients with type 2 diabetes accompanied by hepatic impairment. The present study was undertaken to evaluate the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 11 publications
6
14
0
Order By: Relevance
“…17 In a pooled analysis in 232 Japanese patients, Seko et al also found a significant reduction in plasma ALT with canagliflozin. 18 Similar results have been reported in recent small uncontrolled studies with other SGLT inhibitors, [19][20][21][22][23] some with a reduction in IHTG on liver imaging, [21][22][23] while a larger placebo-controlled study with dapagliflozin did not observe an improvement in IHTG despite a reduction in subcutaneous and visceral fat. 24 Taken together, the role of SGLT2 inhibitors on IHTG and glucose metabolism remains unclear.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…17 In a pooled analysis in 232 Japanese patients, Seko et al also found a significant reduction in plasma ALT with canagliflozin. 18 Similar results have been reported in recent small uncontrolled studies with other SGLT inhibitors, [19][20][21][22][23] some with a reduction in IHTG on liver imaging, [21][22][23] while a larger placebo-controlled study with dapagliflozin did not observe an improvement in IHTG despite a reduction in subcutaneous and visceral fat. 24 Taken together, the role of SGLT2 inhibitors on IHTG and glucose metabolism remains unclear.…”
Section: Introductionsupporting
confidence: 80%
“…In humans, 2 pooled analyses reported a decrease in plasma aminotransferases with canagliflozin treatment that correlated with the magnitude of body weight loss. A reduction in ALT and/or IHTG has been reported in small, open‐label studies of 5‐ to 6‐months duration with luseogliflozin, ipragliflozin, and empagliflozin, associated with reductions in BMI, visceral fat, and HbA1c. Tobita et al showed additional improvement in histology in a small, uncontrolled study in patients with biopsy‐proven NASH .…”
Section: Discussionmentioning
confidence: 86%
“…An open‐label, non‐randomized clinical study involving 79 patients concluded that luseogliflozin significantly ameliorated alanine transaminase, aspartate transaminase, as well as γ‐glutamyl transpeptidase levels in patients suffering from hepatic impairment in conjunction with T2DM. These results indicate towards the potential application of luseogliflozin in the therapy of T2DM patients with liver injury . Another clinical study investigating the efficaciousness of canagliflozin in the treatment of patients with high alanine transaminase levels indicated a beneficial effect of canagliflozin in improving liver function …”
Section: Effect Of Sglt2 Inhibitors On Hepatic Disordersmentioning
confidence: 71%
“…These results indicate towards the potential application of luseogliflozin in the therapy of T2DM patients with liver injury. 26 Another clinical study investigating the efficaciousness of canagliflozin in the treatment of patients with high alanine transaminase levels indicated a beneficial effect of canagliflozin in improving liver function. 27…”
Section: Effec T Of Sg Lt2 Inhib Itor S On Hepatic D Isorder Smentioning
confidence: 99%
“…Four of these reported randomized, controlled, double-blind studies of liraglutide with a placebo (n = 3) or active (n = 1) comparator, and only one of these, the "Liraglutide Safety and Efficacy in Patients with Non-alcoholic Steatohepatitis (LEAN)" study, assessed histological endpoints using biopsy. Of note, of studies investigating liraglutide, only Insufficient data: 3 of 6 studies suggest modest benefit (7,36,38) and the other 3 suggest no benefit over comparator (30,37,59) Topiramate…”
Section: Glp-1 Agonistsmentioning
confidence: 99%